EFFECT OF ZEOLITE ADDITION IN THE DIET ON LOGMANN BROWN EGG QUALITY IN THE SECOND PRODUCTION - Riyanti, Riyanti; Purwaningsih, Nining (Jurnal Zeolit Indonesia, 2004)
Egg shape of second phase production (40- 70 weeks age) of layer bigger than egg shape of one phase production, but egg shell less thickly so than more perishable. On the other side 3.5-4% Ca in the diet only 50% can be absorbed in the intestinal. Ca absorption and Ca retention can be raised by supplementary zeolite in the diet. This experiment was conducted to observe the effect of supplying zeolite in the diet of 192 lohmann brown layer on the egg quality of second phase production. Different feeding treatment was carried out four each group. Layer in treatment 1 were fed control diet; treatment 2, a control diet + zeolite 1.5%; treatment 3, a control diet + zeolite 3%; and treatment 4, a control diet + zeolite 4%. 96 eggs sampel from layer experiment kept on 15 days. The result showed that supplementary zeolite in the diet was significantly ( P â¤ 0.05) increased the thickness of egg shell, significantly (Pâ¤0.05) decreased of egg weight, significantly (Pâ¤ 0.05) decreased air cell, significantly (Pâ¤0.05) increased Haugh Unit (HU) score, and significantly (Pâ¤ 0.05) decreased pH albumen of egg in the second phase production.